IMPLEMENTATION OF THE ENGLISH PREMIER LEAGUE'S INVOLVEMENT IN CAMPAIGNING THE ANTI-RACISM MOVEMENT - Yubel, Novrel Esa; Reuspatyono, Reuspatyono (Journal of Social Political Sciences, 2022)
The issue of racism is still common, especially in the black race. Black people are often subjected to discriminatory treatment, such as violence to slurs. The death of George Floyd in 2020 adds to the dark history of racism, and this has further strengthened the campaign against the importance of anti-racism to black citizens through the slogan "Black Lives Matter". The spread of this slogan has made this campaign spread to transnational society, including the administrators and athletes in the English Premier League (EPL). This research focuses on discussing the role of the EPL in the anti-racism movement through the Black Lives Matter campaign, where the research question is: "how is the implementation of the involvement of the English Premier League in campaigning for the anti-racism movement through the "Black Lives Matter" Campaign in the 2019/2020 Season?". The purpose of this study is to explain the role of the EPL in the anti-racism movement through the â€œBlack Lives Matterâ€ campaign, as well as the implementation of its campaign. This study uses a literature study data collection technique, with secondary data sources from books or reports, and analyzed using descriptive qualitative methods. This research is based on the theory of the British School as well as the concept of Transnational Advocacy Networks (TANs), both of which are used as analytical instruments. Based on the analysis, it is found that the role of EPL in supporting the â€œBlack Lives Matterâ€ campaign is very explicit. This can be seen in the support from the league management (CEO), to the coaches and players. The EPL campaigns in three forms, namely: changing the name on the uniform with the words â€œBlack Lives Matterâ€, installing a slogan logo on the uniform, as well as kneeling on one leg while holding hands up before the match starts. Therefore, it can be concluded that the EPL's role in campaigning for the â€œBlack Lives Matterâ€ issue is manifested through real actions that refer directly to the slogan campaign.